Iranian Librarians' Electronic Communications: A Case Study of a Discussion Group - Shima Moradi; Mohadesseh Dokhtesmati (Universiti Sains Islam Malaysia, 2024)
Presenter from LIS Ph.D. Student. Science & Research Branch, Islamic Azad University